Classification of Culturable Bifidobacterial Population from Colonic Samples of Wild Pigs (Sus scrofa) Based on Three Molecular Genetic Methods - Pechar, Radko; Killer, Jiří; Mekadim, Chahrazed; Geigerová, Martina; Rada, Vojtěch (Current microbiology, 2017)
Occurrence of bifidobacteria, known as health-promoting probiotic microorganisms, in the digestive tract of wild pigs (Sus scrofa) has not been examined yet. One hundred forty-nine fructose-6-phosphate phosphoketolase positive bacterial strains were isolated from colonic content of twenty-two individuals of wild pigs originated from four localities in the Czechia. Based on PCR-DGGE technique targeting the variable V3 region of the 16S rRNA genes, strains were initially differentiated into four groups represented by: (i) probably a new Bifidobacterium species (89 strains), (ii) B. boum/B. thermophilum/B. thermacidophilum subsp. porcinum/B. thermacidophilum subsp. thermacidophilum (sub)species (49 strains), (iii) Pseudoscardovia suis (7 strains), and (iv) B. pseudolongum subsp. globosum/B. pseudolongum subsp. pseudolongum (4 strains), respectively. Given the fact that DGGE technique did not allow to differentiate the representatives of thermophilic bifidobacteria and B. pseudolongum subspecies, strains were further classified by the 16S rRNA and thrS gene sequences. Primers targeting the variable regions of the latter gene were designed to be applicable in identification and phylogeny of Bifidobacteriaceae family. The 16S rRNA-derived phylogenetic study classified members of the first group into five subgroups in a separated cluster of thermophilic bifidobacteria. Comparable results were obtained by the thrS-derived phylogenetic analysis. Remarkably, variability among thrS sequences was higher compared with 16S rRNA gene sequences. Overall, molecular genetic techniques application allowed to identify a new Bifidobacterium phylotype which is predominant in the digestive tract of examined wild pigs.
Keywords: Animals; Bifidobacterium; Molecular Typing; Sus scrofa; bakteriální geny; RNA, Ribosomal, 16S; divoká zvířata; gastrointestinální trakt; prasata; molekulární typizace; Phylogeny; Animals, Wild; Swine; Sequence Analysis, DNA; Genes, Bacterial; zvířata; sekvenční analýza DNA; Gastrointestinal Tract; fylogeneze; RNA ribozomální 16S